Activities of Heterogeneous Acid-Base Catalysts for Fragrances Synthesis: A Review - Mardi Santoso; Sugeng Triwahyono; Hartati Hartati; Didik Prasetyoko (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
This paper reviews various types of heterogeneous acid-base catalysts for fragrances preparation. Catalytic activities of various types of heterogeneous acid and base catalysts in fragrances preparation, i.e. non-zeolitic, zeolitic, and mesoporous molecular sieves have been reported. Generally, heterogeneous acid catalysts are commonly used in fragrance synthesis as compared to heterogeneous base catalysts. Heteropoly acids and hydrotalcites type catalysts are widely used as heterogeneous acid and base catalysts, respectively. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)